2009
DOI: 10.1063/1.3168650
|View full text |Cite
|
Sign up to set email alerts
|

Observation of an anomalous correlation between permittivity and tunability of a doped (Ba,Sr)TiO3 ferroelectric ceramic developed for microwave applications

Abstract: Anomalous dependencies of the dynamic (pulse) and static tunability [k(U)=C(0)/C(U)] as a function of permittivity (ε) were observed in ferroelectric varactors based on doped paraelectric state (Ba,Sr)TiO3 ceramics. The reduction of the relatively high permittivity value from ε≅810 down to ε≅260 by introducing various proportions of a Mg2TiO4 additive resulted in a 20% increase in tunability. Furthermore, ceramics with this additive have demonstrated dynamic tunability noticeably higher than the static tunabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 9 publications
1
16
0
1
Order By: Relevance
“…The seemingly contradictory results between Ref. and maybe results from different Mg 2 TiO 4 content range. To date, only Kozyrev et al .…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The seemingly contradictory results between Ref. and maybe results from different Mg 2 TiO 4 content range. To date, only Kozyrev et al .…”
Section: Introductionmentioning
confidence: 84%
“…In the Ba 0.5 Sr 0.5 TiO 3 –Mg 2 TiO 4 system, with the increase in Mg 2 TiO 4 content from 50 to 80 wt%, the dielectric constant at 10 kHz decreased from 335 to 35, and the tunability at 3 kV/mm decreased from 18.4% to 10.8% . More recently, Kozyrev et al . reported that increasing Mg 2 TiO 4 content from 8.3 to 44.4 wt% led to the decrease in dielectric constant of BST–Mg 2 TiO 4 from 810 to 260, but the tunability increased anomalously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, this phenomenon is considered to be an anomaly, because the linear dielectric has no nonlinear property. However, in the studies of Kozyrev et al . and Nenasheva et al., with increasing Mg 2 TiO 4 content in BST‐Mg 2 TiO 4 composite ceramics from 8.3 to 44.4 wt%, the tunability increased.…”
Section: Resultsmentioning
confidence: 92%
“…[1][2][3] Moreover, materials that have coupled electric, magnetic, and structural order parameters that result in simultaneous ferroelectricity, ferromagnetism, and ferroelasticity are known as multiferroics. [4][5][6] These multiferroics materials have attracted a lot of attention in recent years because they can potentially offer a whole range of new applications, including nonvolatile ferroelectric memories, novel multiple state memories, and devices based on magnetoeletric effects.…”
Section: Introductionmentioning
confidence: 99%